Semiautomatic crimping machine - Nosek, Jakub; Štohl, Radek (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2024)
This document deals with explanation of the design, creation and testing of a new automated machine for the production of ureteral catheters for a company producing medical equipment. The work is a continuation of the diploma thesis of a student of the College of Polytechnics Jihlava, whose work only concerned the design of the mechanical part of the machine and the analysis of the actual manual production process.
Keywords: PLC; TIA Portal; HMI; machine safety; EPLAN